PENGARUH METODE OUTDOOR STUDY TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN IPAS DI KELAS IV SD NEGERI 158501 SIBULUAN - Pasaribu, Stela Octavia; Theresia, Monica; Sabri, Sabri; Nasution, Sartika Rati Asmara (Program Studi Pendidikan Guru Sekolah Dasar Fakultas Pendidikan Ilmu Pengetahuan Sosial dan Bahasa Institut Pendidikan Tapanuli Selatan, 2025)
This research aims to determine the effect of using the outdoor study method on social studies learning outcomes regarding norms and customs in my area, class IV at SD Negeri 158501 Sibuluan. The method used is quantitative experimental research using a one group pretest and posttest design. The subjects in this research were 20 students in class IV B of SD Negeri 158501 Sibuluan. The data collection technique uses a test in the form of 10-item multiple choice questions, 5 questions and 5 questions essay. Manual data analysis techniques include Normality Test, Homogeneity Test, Hypothesis Test . From the results of observations made on the homeroom teacher in class IV B of SD Negeri 158501 Sibuluan through indicators by submitting 23 statement items, an average score of 89.16 was obtained. If the assessment criteria were consulted, the score was in the